2014
DOI: 10.1093/jscr/rjt128
|View full text |Cite
|
Sign up to set email alerts
|

Breast filariasis

Abstract: Filarial involvement of breast is a rare entity. Here is an unusual case of an old lady with right breast lump with axillary lymphadenopathy mimicking breast carcinoma, cytologically diagnosed as filarial mastitis. The patient subsequently received antihelmenthic therapy and showed marked clinical response within few weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A female worm gives rise to 50,000 microfilaria/day. 8 Intact worms produce minimal tissue reaction while degenerating parasites provoke inflammatory cell infiltrationmainly eosinophils and occasionally the development of epitheloid granulomas. The involved lymphatic vessels are eventually blocked and replaced by fibrous tissue, and the patient may present with a palpable breast mass i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A female worm gives rise to 50,000 microfilaria/day. 8 Intact worms produce minimal tissue reaction while degenerating parasites provoke inflammatory cell infiltrationmainly eosinophils and occasionally the development of epitheloid granulomas. The involved lymphatic vessels are eventually blocked and replaced by fibrous tissue, and the patient may present with a palpable breast mass i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Filaria of the breast with axillary lymphadenopathy and lymphedema, mimicking breast carcinoma has been previously reported. [2] Microfilariae have also been previously observed as coincidental findings of various neoplastic conditions. [3] Also, cytological evidence of lymphatic filariasis coexistent with breast carcinoma has been previously documented,[4] but histologically confirmed reports are still rare.…”
Section: Introductionmentioning
confidence: 99%
“…So, in case of fluid aspirate and pauci cellular smear from breast lump careful screening with possibilities of microfilarial infestation particularly in endemic area should be done to avoid unnecessary surgery.In our study one case was reported from breast swelling. Pal S. et al, Thakur et al and Patrikar et al have reported microfilariasis in breast lump [13][14][15].…”
mentioning
confidence: 98%